Clausewitz in his time : essays in the cultural and intellectual history of thinking about war - Paret, Peter (Berghahn Books, 2015)
Anything but a detached theorist, Clausewitz was as fully engaged in the intellectual and cultural currents of his time as in its political and military conflicts. Late-eighteenth century thought helped shape the analytic methods he developed for the study of war. The essays in this volume follow his career in a complex military society, together with that of other students of war, both friends and rivals, providing a broad perspective that leads to significant documents so far unknown or ignored. They add to our understanding of Clausewitz's early ideas and their expansion into a comprehensi.